Assessing the performance of the national park authorities: a case study of Northumberland National Park, England. Issue 5 (28th July 2016) - Austin, Richard; Garrod, Guy; Thompson, Nicola
Abstract : Although the legislation for the designation of national parks in England dates back to the National Parks and Access to the Countryside Act of 1949, it was not until 1997 that free-standing and independent national park authorities were established to help manage these landscapes. In 2014–15, the 10 English national park authorities were allocated £44.6 million from the Department for Food, the Environment and Rural Affairs to deliver their conservation and recreation purposes and their socio-economic duty. This paper discusses how the performance of the national park authorities has been assessed, using the Northumberland National Park Authority as a case study.